1983
DOI: 10.2307/3898202
|View full text |Cite
|
Sign up to set email alerts
|

Diethylstilbestrol as a Temporary Chemosterilant to Control Black-Tailed Prairie Dog Populations

Abstract: Controlling reproduction in pest rodent populations may be preferable to using lethal rodenticides. The effectivenss of diethylstilbestrol (DES), a synthetic estrogen, as a reproductive inhibitor in female bhtck-tailed prairie dogs (Cyuomys ludovicianus) was examined in a 4-year study at Wind Cave Nationnl Park, South Dakota. In 1979 and 1980, a study colony was monitored to determine age structure, reproductive success of individual animals, and rate of colony expansion. In 1981, the colony was divided into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The age ratio again was divided evenly in 1981, perhaps because of the effects of treatment of half of the females with diethylstilbestrol during the 1981 breeding season. Reproduction was reduced significantly for that year (Garrett and Franklin, 1983). However, after a second treatment with diethylstilbestrol in 1982, the age ratio again was skewed in favor of juveniles (x2 = 19.99, d.f.…”
Section: Population Attributesmentioning
confidence: 98%
See 1 more Smart Citation
“…The age ratio again was divided evenly in 1981, perhaps because of the effects of treatment of half of the females with diethylstilbestrol during the 1981 breeding season. Reproduction was reduced significantly for that year (Garrett and Franklin, 1983). However, after a second treatment with diethylstilbestrol in 1982, the age ratio again was skewed in favor of juveniles (x2 = 19.99, d.f.…”
Section: Population Attributesmentioning
confidence: 98%
“…We found a male-skewed sex ratio in the prereproductive age class of intercolony and intracolony dispersers, male intercolony dispersers moved farther than females, and the behavior of residents of the study colony operated to prevent incest. Females of the study colony commonly bred as yearlings (Garrett and Franklin, 1983), but only with an unrelated male. Older males usually moved to different coteries before their daughters attained breeding age (Hoogland, 1982; this study, n = 3).…”
Section: Proximate Factorsmentioning
confidence: 99%
“…Furthermore, the drugs can be injected by dartfiring rifle, thus precluding the need for capture and handling. Similarly, Garrett and Franklin (1983) found that prairie dog ( Cynomys ludovicianus) populations could be controlled by feeding the animals estrogen-laced grain. These colonially living rodents are highly seasonal breeders, and hormones need only be administered during a short period of time to have a significant impact on reproduction.…”
Section: Problems Of Population Regulationmentioning
confidence: 96%
“…Garrett and Franklin (1982) in addition experimented with visual barriers as a means of reducing, halting or directing the expansion of dogtowns. Garrett and Franklin (1983) and later Klukas (unpublished) used Diethylstilbestrol (DES) to determine if prairie dog population management could be achieved by limiting natality. Population regulation through use of smoke bombs, rim and center fire rifles and zinc phosphide was also tested by park personnel.…”
Section: Research Focused On Management Questionsmentioning
confidence: 99%